Transthyretin amyloid polyneuropathies mimicking a demyelinating polyneuropathy. (10th July 2018) - Lozeron, Pierre; Mariani, Louise-Laure; Dodet, Pauline; Beaudonnet, Guillemette; Théaudin, Marie; Adam, Clovis; Arnulf, Bertrand; Adams, David
Abstract : Objective: To clearly define transthyretin familial amyloid polyneuropathies (TTR-FAPs) fulfilling definite clinical and electrophysiologic European Federation of Neurological Societies/Peripheral Nerve Society criteria for chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: From a cohort of 194 patients with FAP, 13 of 84 patients (15%) of French ancestry had late-onset demyelinating TTR-FAP. We compared clinical presentation and electrophysiology to a cohort with CIDP and POEMS (polyneuropathy, organomegaly, endocrinopathy, monoclonal protein, and skin changes) syndrome. We assessed nerve histology and the correlation between motor/sensory amplitudes/velocities. Predictors of demyelinating TTR-FAP were identified from clinical and electrophysiologic data. Results: Pain, dysautonomia, small fiber sensory loss above the wrists, upper limb weakness, and absence of ataxia were predictors of demyelinating TTR-FAP ( p < 0.01). The most frequent demyelinating features were prolonged distal motor latency of the median nerve and reduced sensory conduction velocity of the median and ulnar nerves. Motor axonal loss was severe and frequent in the median, ulnar, and tibial nerves ( p < 0.05) in demyelinating FAP. Ulnar nerve motor amplitude <5.4 mV and sural nerve amplitude <3.95 μV were distinguishing characteristics of demyelinating TTR-FAP. Nerve biopsy showed severe axonal loss and occasional segmental demyelination-remyelination. Conclusion: Misleading features of TTR-FAP fulfilling criteria for CIDP are not uncommon in sporadic late-onset TTR-FAP, which highlights the limits of European Federation of Neurological Societies/Peripheral Nerve Society criteria. Specific clinical aspects and marked electrophysiologic axonal loss are red flag symptoms that should alert to this diagnosis and prompt TTR gene sequencing.